INTRODUCTION: HERTA MÜLLER AND THE CURRENTS OF EUROPEAN HISTORY - Brigid Haines (German Life and Letters, 2020)
Ten years on from the award to her of the Nobel Prize in Literature and twenty years after German reunification and the fall of the Ceausescu regime in Romania this volume of essays by international scholars revisits Herta Müller’s work and places it within broader intellectual, geographical, and historical horizons than has hitherto been attempted. It also reconciles the public intellectual with the literary author. For while it has long been clear that Müller’s aesthetically innovative and highly acclaimed novels, essays, and collages stand as a testament to the major upheavals of twentieth-century European history, her self-adopted role as moral voice and her willingness to make broad historical comparisons over the past three decades have often met with controversy. The broad relevance of Müller’s ethical and political concerns – central, we argue here, to both her literary work and her public statements – has been underestimated in both the feuilleton and scholarly criticism in favour of a focus on the historical interest of her life under Romanian communism. But her warnings regarding the vulnerability of the West’s post-war settlement, denazification and the stability of Europe, received by some as tiresome ten years ago, are, at the time of writing, thrown into sharp relief by the greatest humanitarian crisis Europe has faced since 1945 – the so-called refugee crisis – and by the global rise of populism. Put plainly, the complacency that might previously have allowed Müller’s interventions on the topics of xenophobia, nationalism, flight, and expulsion to be regarded as pertaining solely to Europe’s pre-1989 history is no longer sustainable.